Pengaruh Kompetensi Aparatur Desa, Pemanfaatan Teknologi Informasi Dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Di Kecamatan Purbolinggo - Furqoningrum, Destri; Zanaria, Yulita; Rahayu, Sri Retnaning (Universitas Muhammadiyah Metro, 2022)
This study aims to analyze the Effect of Competency of Village Apparatus 1; Utilization of Information Technology 2; and Community Participation 3; Against Village Fund Management Accountability 4; in Purbolinggo District. The type of research used in this study is quantitative with a descriptive approach, in this study researchers used primary data through questionnaires and the population in this study amounted to 247 respondents then the sampling technique in this research used purposive sampling by using several respondent criteria so that 108 respondents were obtained. The results of this study indicate that Village Apparatus Competence has a positive and significant effect on Village Fund Management Accountability, Information Technology Utilization has a positive and significant impact on Village Fund Management Accountability, and Community Participation has a positive and significant impact on Village Fund Management Accountability in Purbolinggo District.